Strategic Human Resource Management and Organizational Competitiveness: A Resource-Based Empirical Analysis - Yani Restiani Widjaja; Ersha Faturochman; Nursaimatussaddiya Nursaimatussaddiya (Global Research Collaboration, 2026)
In increasingly competitive organizational environments, human resources are no longer viewed as administrative support but as strategic assets that shape organizational capability. However, empirical evidence examining how Strategic Human Resource Management (SHRM) directly contributes to organizational competitiveness, particularly in regional contexts such as West Java, remains limited. This study aims to examine the effect of SHRM implementation on organizational competitiveness and to test whether strategic HR practices significantly enhance competitive capacity. The study employed a quantitative cross-sectional survey design involving 210 respondents from managerial, supervisory, and HR-related positions across organizations in West Java. Data were collected using structured questionnaires measured on a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicate that SHRM has a positive and significant effect on organizational competitiveness (β = 0.672; t = 12.845; p < 0.001). The model explains 45.2% of the variance in organizational competitiveness (R² = 0.452), indicating moderate explanatory power. These findings demonstrate that strategic alignment, employee development, performance management, and talent utilization play critical roles in enhancing adaptability, service quality, and organizational responsiveness. This study confirms that SHRM functions as a strategic driver of organizational competitiveness rather than merely an administrative mechanism. The findings extend the Resource-Based View by providing empirical evidence from a regional Indonesian context and offer practical implications for organizations to strengthen competitive advantage through strategic HR alignment.